Migrants Metaphors, Nimbly-footed Adventurers and the Imaginaries of ‘Home’ in Eric Ngalle’s I, Eric Ngalle - Udoinwang, David Ekanem; Enukora, Elizabeth N. (NIU Journal of Humanities, 2024)
Contemporary migrant narratives primarily centralise the wave of movements of largely young people from the lowly-endowed third world nations, northward, defying known and unknown perils and uncertainties that attend to such journeys into the ever-attractive Euro-America economic zones. This phenomenon proffers fertile site for creativity and critical scholarly engagements. This work examines the socio-cultural contexts of the imaginaries of ‘home’ and trauma of homelessness in Eric Ngalle’s novel - I, Eric Ngalle . The work interrogates the novel’s figuration of the historical facades of ‘home’ as signification of cultural roots and tension of memories characteristically depicted in the bulk of narratives of African migrants and the diaspora encounters. The historical import of the nimbly-footed migrants with the concomitant sense of loss and nostalgia that intertwine with the experiences of desperate African migrants in their quests for greener pastures in Europe and other parts of the world, inspires this work. This paper further elucidates the strategies which migrants cope with and the disillusionment they face, including the harsh realities of the experience associated with the situation. The paper concludes by extrapolating the global inequalities, the dire situations in weak third world states, and racial shock that characterise African migrants in the Diasporas that seek economic refuge and better world in Europe. Keywords: Migration phenomenon; parable of ‘home’; ultimate dangers; survival strategies, Eric Ngalle.